Determinations of plasma density and decay time in the hollow cathode discharge by microwave transmission - 张林 何锋 李世超 欧阳吉庭 (Chinese physics B, 2013)
The microwave （MW） transmission method is employed to measure both the plasma density and the plasma decay time in the hollow cathode discharge （HCD） in argon at low pressure. The plasma density in DC-driven or pulsed HCD is on the order of 1012 cm-3, which can block the X-band MW effectively. In the case of pulsed HCD, the MW transmittance shows the same waveform as the pulsed current during the rising edge if the driving frequency is low, but with a longer delay during the falling edge. The MW transmittance reaches a constant low level when the driving frequency is high enough. The plasma decay time in the HCD system is measured to be about 100 μs around a pressure of 120 Pa. The ambipolar diffusion is considered to be the major mechanism in the decay process.